Infectious Proctitis due to Human Mpox. (2nd September 2022) - Gedela, Keerti; Da Silva Fontoura, Dayana; Salam, Alex; Gorman, Gerry; Golden, John; O'Hara, Geraldine; Elowaidy, Ahmed; Tittle, Victoria; Girometti, Nicolo; Whitlock, Gary; Patel, Sheel; Suchak, Tara; et al.
Abstract: We describe 2 cases of infectious proctitis secondary to human monkeypox in patients presenting with rectal pain. These cases highlight the importance of multidisciplinary management of monkeypox and in expanding case definitions and enabling clinical recognition in patients presenting without skin rash.